Decadal NA O signal evolution for the last two millennia in the central Range (Spain) - Sánchez-López, Guiomar; Hernández, Armand; Pla-Rabes, S.; Toro, M.; Granados, I.; Sigrò, Javier; Trigo, Ricardo M.; Rubio de Ingles, Maria Jesus; Sáez, Alberto; Giralt, Santiago (2015)
Meteorological data, ice records and multiproxy analyses of sediment records from two Iberian alpine lakes (Peñalara and Cimera) have been used to determine the decadal impact of the North Atlantic Oscillation (NAO) for the last two millennia in the Central Range, Spain. A conceptual lake model based on Pearson correlation coefficients obtained between season-scale time series of the NAO index, meteorological data and ice phenology records has allowed us to characterize the present day lake-climate-NAO nteractions. The Principal Component Analyses carried out using multiproxy data evidence that changes in the composition of the sediments are the result of fluctuations in precipitation (terrigenous inputs) and lake primary productivity (nutrients inputs). During the negative (positive) phase of NAO the ice-cover lasts longer (shorter) due to wetter (drier) conditions and more (less) snow accumulation on the ice cover, limiting (allowing)the terrigenous inputs. Furthermore, positive phase of NAO is likely related with higher values of lake primary productivity due to the inputs of nutrients from eolian Saharandust. Our results are consistent with long-term reconstructions of southern Europe’s climate and NAO index. The Roman Warm period (0-500 AD) was characterized by humid conditions with a dry end period that is compatible with a change from a predominant NAO-towards a NAO+phase. Dry conditions ersisted during the first half part of The Early Middle Ages(500–900 AD) which showed a transition to wetter conditions dominated by a NAO-phase. The Medieval Climate Anomaly (900-1300 AD) exhibited a similar climate transition, whereas the Little Ice Age (1300-1850 AD) displayed a dry-wet-dry alternation related with shifts in the predominant NAO phase. The last 100 years are characterized by a progressive trend to drier conditions with an evolution from NAO-to NAO+. Peer reviewed